Postoperative Tension Pneumocephalus with Mt. Fuji Sign: A Case Report - Anwer, Majid; Sridhar, Rachith; Kumar, Anil; Kumar, Anurag; Kumar, Abhishek (Indian Journal of Neurotrauma, 2025)
Tension pneumocephalus (TP) is an uncommon but potentially lethal complication of the neurosurgical process. The treatment is usually surgical decompression. We describe here a case of TP following evacuation of subdural hematoma (SDH) and its successful nonoperative management. A 75-year-old elderly male presented to the emergency department with a history of progressive weakness of bilateral upper and lower limbs and altered sensorium for 2 months. His Glasgow Coma Scale was E3V4M6, and pupils were bilaterally equal and reactive to light. A noncontrast computed tomography (NCCT) of the head showed bilateral acute-on-chronic SDH with internal septations and mass effect. The patient was planned and taken for bilateral craniotomy with membranectomy with evacuation of SDH. A repeat NCCT head showed development of bilateral TP with a “Mount Fuji” sign. The patient was placed on high-flow oxygen support and positioned with head-end elevation. Subsequent computed tomography scan showed resolution of intracranial air foci and expansion of the brain. Traumatic pneumocephalus is a dreaded complication of post-neurosurgical procedure. A high index of suspicion based on the clinical and radiological findings helps in identifying TP. Nonoperative management with closed observation is a viable option in clinically silent TP.
Keywords: head injury; Mount Fuji sign; neurosurgical procedure; subdural hematoma; tension pneumocephalus